2015
DOI: 10.1002/elps.201400459
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ζ‐potential, charge, and number of organic ligands on the surface of water soluble quantum dots by capillary electrophoresis

Abstract: The number of charges and/or organic ligands covalently attached to the surface of CdTe quantum dot nanoparticles has been determined from their electrophoretic mobilities measured in capillaries filled with free electrolyte buffers. Three sizes of water soluble CdTe quantum dots with 3-mercaptopropionic and thioglycolic acids as surface ligands were prepared. Their electrophoretic mobilities in different pH and ionic strength values of separation buffers were measured by capillary electrophoresis with laser i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…When compared to methotrexate, quantum dots clearly showed a more effective electrostatic modulation, which could be attributed to higher particle charge and lower ionic strength of the solution. Specifically, the high exposed charge is due to the carboxylic functionalization, where several groups result in a negative net charge that ranges from −5 to −15 depending on pH and ionic strength [ 41 ]. Moreover, the low ionic strength solution (0.01 × PBS) has a Debye length 10 times greater than the 1 × PBS.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to methotrexate, quantum dots clearly showed a more effective electrostatic modulation, which could be attributed to higher particle charge and lower ionic strength of the solution. Specifically, the high exposed charge is due to the carboxylic functionalization, where several groups result in a negative net charge that ranges from −5 to −15 depending on pH and ionic strength [ 41 ]. Moreover, the low ionic strength solution (0.01 × PBS) has a Debye length 10 times greater than the 1 × PBS.…”
Section: Resultsmentioning
confidence: 99%
“…The electric potential formed at this interface is defined as zeta potential (ζ ). 123 To determine the zeta potential an electrical voltage is applied in a special cuvette containing the charged NPs in suspension. The NPs move towards the electrode of opposite polarity at a constant velocity that is proportional to surface charges and consequently the zeta potential.…”
Section: Dynamic Light Scattering and Zeta Potentialmentioning
confidence: 99%
“…124 In addition, a modification process on QDs' surface (e.g., ligand addition) could be also evaluated using zeta potential analysis. 123 Ipe et al 125 reported the use of DLS and zeta potential techniques to confirm the protein cytochrome P450 BSβ conjugation with CdS and CdSe QDs. Upon protein conjugation to CdS QDs' surface, for example, increasing in the hydrodynamic diameter (near to three-fold) and modification in the nanoparticles charge from about ζ = −28 to −5 mV were observed.…”
Section: Dynamic Light Scattering and Zeta Potentialmentioning
confidence: 99%
“…At the aim to clarify these aspects it is important to remind that the electrophoretic behavior of AuNP has been described as strongly depending on the experimental conditions adopted in terms of buffer ionic strength, colloid surface charge and hydrophilic coatings which surely influence the ζ‐potential. For ζ < 25 mV at 25°C, the dependence of the electrophoretic mobility on particle size is expressed as a function of ( kR ), where k is the reciprocal of the electric double layer thickness and R is the particle hydrodynamic radius .…”
Section: Resultsmentioning
confidence: 99%